Kuat Tekan Beton Dengan Dan Tanpa Penambahan Silica Fume Dalam Rendaman Air Laut - Ghozi, Mohammad; Budiati, Anik; Priambada, Agoes Wahyu; Sabariman, Bambang; Suryadi, Akhmad (Fakultas Teknik Universitas Bhayangkara Surabaya, 2025)
Marine concrete is used for structures in marine environments that are susceptible to chemical attacks such as sulfates and chlorides. This study aims to analyze the effect of adding 7% silica fume on the compressive strength of marine concrete soaked in seawater. The experimental research method was carried out by making 12 concrete cylinder samples (diameter 15 cm × height 30 cm), consisting of two variations: concrete without silica fume and concrete with 7% silica fume. Compressive strength testing refers to SNI 03-1974-1990 and ASTM C39, with seawater immersion for 50 days and testing at the ages of 14, 28 and 50 days. The results showed that concrete with 7% silica fume achieved an average compressive strength of 39.90 MPa at the age of 28 days, higher than concrete without silica fume (37.64 MPa). This increase is due to the pozzolanic reaction of silica fume which fills the pores of the concrete and forms calcium silicate hydrate (CSH) compounds, increasing the density of the concrete matrix. The slump value of both concrete variations is stable at 12 cm, meeting the planned workability criteria. This study states that the addition of 7% silica fume is effective in increasing the compressive strength and resistance of marine concrete to the marine environment. Recommendations include the use of silica fume for marine structures, strict supervision in mixing materials, and optimization of mixing time to prevent too fast setting time. This study contributes to the development of environmentally friendly concrete with high durability in coastal areas.